Methodological issues affecting the study of fish parasites. I. Duration of live fish storage prior to dissection - Kvach, Yuriy; Ondračková, Markéta; Janáč, Michal; Jurajda, Pavel (Diseases of aquatic organisms, 2016)
We tested the ability of parasite species to respond quickly to artificial conditions (e.g. by changing abundance or even decreasing to extinction) while host fish species were being held alive prior to dissection. Prussian carp Carassius gibelio were sampled by electrofishing from 2 ponds alongside the River Dyje (Czech Republic) during 'cold' and 'warm' seasons. All fish were transported to the laboratory in aerated pond water and kept in a 1 m3 outdoor basin with aged tap water for 6 d. Twenty fish were dissected on consecutive days (total 120 fish for each site). Our results indicated that there was little change in parasite loading over the first 3 d of holding, suggesting no impact on parasitological studies undertaken over this period. From the fourth day, however, overall parasite abundance increased due to rapid reproduction of some parasite species, especially gyrodactylids in the cold season and dactylogyrids in the warm season. Parasite diversity appeared less stable in the warm season, with significant differences being registered as early as the second day. In addition to holding period, environmental conditions during fish holding will also play an important role in parasite community shifts.
Keywords: časové faktory; Carps; Temperature; Time Factors; Fish Diseases; teplota; kapři; Animals; parazitární nemoci u zvířat; zvířata; nemoci ryb; Parasitic Diseases, Animal